Differential detection of M184V/I between plasma historical HIV genotypes and HIV proviral DNA from PBMCs. (15th May 2020) - Margot, Nicolas; Ram, Renee; McNicholl, Ian; Haubrich, Richard; Callebaut, Christian
Abstract: Background: The M184V/I reverse transcriptase mutation, which confers major resistance to lamivudine and emtricitabine, is still quite frequent in people living with HIV. The underlying presence of the M184V/I mutation may undermine virological outcomes of ART, particularly in the context of proposed treatment with two-drug combinations that include drugs affected by M184V, such as lamivudine. In suppressed patients for whom historical data are seldom available, resistance assays evaluating integrated viral DNA can help select a fully active switch regimen. Objectives: To compare detectability of M184V/I in historical HIV-1 RNA analyses versus HIV-1 DNA sequencing. Methods: We analysed the detection of the M184V/I mutation in a prospective study and compared HIV historical genotypes (plasma) versus integrated HIV DNA (PBMCs) obtained via a validated commercial proviral HIV DNA assay. Eligible participants had HIV-1 RNA <50 copies/mL for ≥6 consecutive months prior to screening. A plasma historical genotypic report (HGR) showing the presence of M184V/I was required for all participants and proviral HIV DNA analysis was conducted prior to enrolment. Results: All 84 participants had evidence of M184V or M184I in their HGR (100%), whereas the mutation was detected in only 40/84 participants by proviral HIV DNA sequencing analysis (48%). Differential detection of M184V/I was not associated with timing differences between the HGR and proviral HIV DNA sampling, the overall duration of ART, or CD4 cell counts and HIV-1 viral load at baseline. Conclusions: Our results suggest that undetected M184V/I should be considered when switching virologically suppressed patients to new regimens, particularly two-drug lamivudine- or emtricitabine-containing combinations.